2008
DOI: 10.1007/s10661-008-0560-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the microbial load of incoming and distal outlet waters from dental unit water systems in Istanbul

Abstract: This is a cross-sectional study of the incoming and distal outlet water quality from 41 dental units in Istanbul, carried out to compare the total microbial loads using traditional culture method versus epifluorescence microscopy. The possible presence of Legionella pneumophila using traditional culture method was also analyzed. One hundred and twenty three samples were taken from the high-speed handpiece lines, air-water syringe lines and source (incoming) water supplies from 41 dental units. The samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Research shows that that the mean concentration of microorganisms in reservoir water was: >3.9 × 10 4 ; 6.6 × 10 4 ; 2.01 × 10 5 ; or 0–1.52 × 10 6  cfu/ml (Szymańska et al 2008). In later studies, the detected concentration reached 3.17 × 10 5  cfu/ml (Türetgen et al 2009). Our study found that the mean concentration of aerobic and facultative anaerobic bacteria in water from 107 reservoirs was 1.1 × 10 5  cfu/ml, which is lower than the results most frequently obtained in other studies.…”
Section: Discussionmentioning
confidence: 92%
“…Research shows that that the mean concentration of microorganisms in reservoir water was: >3.9 × 10 4 ; 6.6 × 10 4 ; 2.01 × 10 5 ; or 0–1.52 × 10 6  cfu/ml (Szymańska et al 2008). In later studies, the detected concentration reached 3.17 × 10 5  cfu/ml (Türetgen et al 2009). Our study found that the mean concentration of aerobic and facultative anaerobic bacteria in water from 107 reservoirs was 1.1 × 10 5  cfu/ml, which is lower than the results most frequently obtained in other studies.…”
Section: Discussionmentioning
confidence: 92%
“…Water for testing was taken from four sites of the DUWLs, including handpieces, air/water syringes, the reservoir bottle, the cup filler outlet and one water tap. According to the literature, contamination of DUWLs has been documented in scientific reports, and microbial levels of 10 4 –10 6 CFU/mL have been reported in DUWL water samples. In our study, the maximum concentration of bacteria in water from the 58 handpieces was 1.8 × 10 6 CFU/mL, which is higher than that reported by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A high number of microorganisms have been found in DUWLs (Walker et al , 2004; Göksay et al , 2008; Dogruöz et al , 2012). Although most microorganisms are harmless, potential pathogens such as Legionella, Pseudomonas, and Candida also have been detected (Walker et al , 2004; Türetgen et al , 2009). These microorganisms are of particular concern because of their ability to cause pneumonia, and other respiratory infections while wound infections are immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies concerning the high levels of bacterial contamination, but little is known about fungal contamination in DUWLs (Williams et al , 1993; Barbeau et al , 1996; Genc et al , 1997; Walker et al , 2000; Walker et al , 2004; Szymanska, 2005a; Göksay et al , 2008; Türetgen et al , 2009). Candida spp.…”
Section: Introductionmentioning
confidence: 99%